Nutrition-based incentives in dairy contract farming in northern Senegal - Bernard, Tanguy; Hidrobo, Melissa; Le Port, Agnès; Rawat, Rahul (Wiley, 2019)
In developing countries contract farming faces numerous challenges that many times lead to its failure. Innovations that help overcome the difficulties of contracting with a large pool of small farmers in such settings can enhance the viability of such schemes. We use a randomized control trial design combined with high frequency data to investigate the impact of adding a nutrition‐based incentive in contracts between a Senegalese dairy processing factory and its semi‐nomadic milk suppliers. The incentive rewarded suppliers for consistent milk deliveries with daily delivery of a micro‐nutrient fortified yogurt for each young child in corresponding households. Findings show large and significant impacts on the frequency and amount of milk delivered, albeit limited to the dry season. We also find larger impacts on milk deliveries when contracts are managed by women.